Hope therapy brings hope: an empirical study of a curriculum intervention to enhance school adaptation of Chinese high school freshmen - Deng, Zuobing; Yang, Rui; Li, Ning; Wei, Xin; Li, Yan (Frontiers in Psychology, 2025)
Adolescents often face significant school adaptation challenges during the school transition period, which may negatively affect their academic performance, emotional well-being, and long-term development. However, research on school adaptation interventions remains limited, especially in applying hope therapy within large-scale, curriculum-based models in the Chinese high school context. This study examined the empirical effects of an 8-week mental health intervention curriculum based on hope therapy in enhancing school adaptation with Chinese freshmen high school students. A pretest revealed that the natural stabilization time for freshmen school adaptation was the ninth week after enrollment. A subsequent formal intervention experiment used a pre- and post-test randomized group control design to divide 444 students into matched experimental and control groups. The experimental group participated in eight psychological intervention sessions based on hope therapy, and the control group received regular mental health lessons. Results showed that the experimental group’s hope level and school adaptation significantly increased after the intervention, not only exceeding those of the pre-intervention level, but also significantly higher than those of the control group. Cross-lagged modeling results further revealed that hope levels at earlier time points significantly predicted subsequent school adaptation, while the reverse effect was not significant. These results collectively support the validity and applicability of hope therapy in improving adolescents’ school adaptation, and provides innovative and alternative intervention perspectives and practice guidelines for high school mental health education, with a strong focus on raising youths’ hope to develop meaningful lives.